2015
DOI: 10.5535/arm.2015.39.4.616
|View full text |Cite
|
Sign up to set email alerts
|

The Dose-Related Effects of Extracorporeal Shock Wave Therapy for Knee Osteoarthritis

Abstract: ObjectiveTo investigate the dose-related effects of extracorporeal shock wave therapy (ESWT) for knee osteoarthritis.MethodsSeventy-five subjects were recruited, 60 of which met the inclusion criteria. The patients were randomly classified into two groups: group L, which was a low-energy group (n=30; 1,000 shocks/session; energy flux density [EFD], 0.040 mJ/mm2) and group M, which was a medium-energy group (n=30; 1,000 shocks/session; EFD, 0.093 mJ/mm2). For each group, 1,000 shock waves were delivered to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
1
47
3
Order By: Relevance
“…Some studies included in our review concluded that the biological efficacy of LI-ESWT was dosage dependent [25]. It seemed that more pulses would bring better biological efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies included in our review concluded that the biological efficacy of LI-ESWT was dosage dependent [25]. It seemed that more pulses would bring better biological efficacy.…”
Section: Discussionmentioning
confidence: 98%
“…There are only 2 previous human studies, and these studies proved that ESWT is effective in reducing pain and improving knee function. However, only the clinical outcomes related to knee OA were assessed, and the substantial morphological or hemodynamic changes in the knee joints were not included [2021]. …”
Section: Discussionmentioning
confidence: 99%
“…A recently published study reported that medium energy (0.093 mJ/mm 2 ) ESWT was more effective in relieving pain and improving functional outcomes than low energy (0.040 mJ/mm 2 ) ESWT. However, histological or molecular safety evaluations were not carried out in that study [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The men's age and the length of time with ED did not affect the results. We acknowledge several limitations, including the lack of a placebo group and to date no long term follow up [23][24][25].…”
Section: Introductionmentioning
confidence: 99%